2014
DOI: 10.1037/a0035450
|View full text |Cite
|
Sign up to set email alerts
|

Brooding rumination and heart rate variability in women at high and low risk for depression: Group differences and moderation by COMT genotype.

Abstract: There is growing evidence that rumination, perhaps specifically brooding rumination, is a core feature of depression and that it contributes to the development and maintenance of the disorder. A separate line of research has highlighted the role played by heart rate variability (HRV). Importantly, both appear to be driven by disruption in the same neural circuit, heightened amygdala reactivity combined with decreased prefrontal control, and both are highlighted in different units of analysis as reflecting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 70 publications
6
33
0
1
Order By: Relevance
“…Thus, in addition to cognitive and behavior therapy, a pharmacological or neurobehavioral intervention might be effective in alleviating rumination by targeting amygdala reactivity. A genetic analysis of the putatively maladaptive component of rumination, known as brooding rumination, found that the COMT Val158Met genotype (which is linked to heightened amygdala reactivity and deficits in prefrontal functioning) was indeed associated with brooding rumination as well as heart rate variability (which is part of the same neural circuit) (Woody et al 2014), adding to the scientific understanding of rumination's many distal risk factors.…”
Section: Offshoots Of Susan Nolen-hoeksema's Workmentioning
confidence: 99%
“…Thus, in addition to cognitive and behavior therapy, a pharmacological or neurobehavioral intervention might be effective in alleviating rumination by targeting amygdala reactivity. A genetic analysis of the putatively maladaptive component of rumination, known as brooding rumination, found that the COMT Val158Met genotype (which is linked to heightened amygdala reactivity and deficits in prefrontal functioning) was indeed associated with brooding rumination as well as heart rate variability (which is part of the same neural circuit) (Woody et al 2014), adding to the scientific understanding of rumination's many distal risk factors.…”
Section: Offshoots Of Susan Nolen-hoeksema's Workmentioning
confidence: 99%
“…With regard to the cardiac response, we predict increased HRV in response to social feedback, with a specific increase in blocks receiving predominantly negative (as compared to positive) social feedback (taken into account tonic HRV, e.g., Thayer et al, 2009;Thayer & Lane, 2000). We expect depressive brooding, a maladaptive form of emotion regulation, to be inversely correlated to HRV -controlled for the tonic HRV at baselineduring the social feedback (Woody et al, 2014;Pieper et al, 2007). Because rumination has been found to be positively associated with gaze fixation and pupil dilation in the processing of emotional material (e.g., Duque, Sanchez, & Vazquez, 2014), we will also explore the association between depressive brooding and both of these latter physiological indices.…”
mentioning
confidence: 99%
“…Even though some inconsistencies exist (e.g., Rottenberg, 2007), meta-analyses and systematic reviews propose both higher tonic and phasic HRV to be a physiological marker of emotion regulation and stress-adaptability (e.g., Park et al, 2014;Thayer et al, 2012;Thayer, Hansen, Saus-Rose, & Johnsen, 2009;Thayer & Lane, 2000). Moreover, depressive brooding, a maladaptive ruminative thinking style that plays a key role in the onset and maintenance of depression has been associated with lower tonic HRV (Woody et al, 2014). Similarly, HRV decreases in response to stress and worry (Delaney & Brodie, 2009;Pieper, Brosschot, van der Leeden, & Thayer, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…State rumination was assessed using self-report measures. Since self-report measures are susceptible to demand effects and rumination has been associated with HRV (e.g., Ottaviani et al 2009;Woody et al 2014), HRV was included as a dependent variable to measure the physiological correlate of rumination. HRV refers to the variation in inter-beat-intervals between normal heartbeats.…”
Section: Introductionmentioning
confidence: 99%